Real estate : an introduction to the profession - Jacobus, Charles J. (Cengage Learning, 2010)
Helps you prepare to pass the real estate license exam for a career in real estate. This book introduces the fundamental principles of real estate with examples. It gives you a perspective on the business equipping you to effectively apply modern real estate practice